PERANAN PENERAPAN SERTIFIKASI GURU TERHADAP KINERJA GURU (INTEGRASI PSIKOLOGI INDUSTRI DAN ORGANISASI ISLAMI) - Budiman Budiman (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2018)
Teachers are the leaders in creating quality and independent human resources. The primary purpose of this research is to examine the role of applying teacher certification to teacher performance. the hypothesis of this research is that there is a role of applying teacher certification to teacher performance. This research type is quantitative approach with development research with sample in this research amounted to 33 teachers in work area DISDIKPORAPAR Banyuasin Regency rayon 1 Banyuasin III District. Methods of data collection in this study use the scale of teacher performance and scale of application of teacher certification. Data collected were analyzed using simple linear regression. The result of the data analysis indicated that there was a significant role in the implementation of teachers' certification in teacher performance (r = 0,756 p = 0.000) meaning that the implementation of teacher certification has a real role to the performance of teachers. It should be the stakeholders of the education and government providers in order to improve and improve the quality of teachers' welfare as a form of appreciation for the efforts and achievements that teachers have achieved.